2007
DOI: 10.1007/s11146-007-9035-9
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Street Layout and Property Value: The Interaction of Accessibility and Land Use Mix

Abstract: New Urbanism, Space syntax, Neighborhood design, Housing prices, R14, R29, R52,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(102 citation statements)
references
References 27 publications
(33 reference statements)
6
92
0
4
Order By: Relevance
“…They include street connectivity, sidewalk availability (McCormack et al 2012), expert opinion (Saelens, Sallis, and Frank 2003), residents' perception , census data, and land-use mix (Matthews, and Turnbull 2007). Given the large number of potential factors that can be used to quantify built environment, Frank et al (2010) introduced the concept of "walkability index" based on conceptual and empirical literature data, by factoring density, mixed land use, and connectivity.…”
Section: Methods To Quantify Walkable Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…They include street connectivity, sidewalk availability (McCormack et al 2012), expert opinion (Saelens, Sallis, and Frank 2003), residents' perception , census data, and land-use mix (Matthews, and Turnbull 2007). Given the large number of potential factors that can be used to quantify built environment, Frank et al (2010) introduced the concept of "walkability index" based on conceptual and empirical literature data, by factoring density, mixed land use, and connectivity.…”
Section: Methods To Quantify Walkable Environmentmentioning
confidence: 99%
“…Over the past decade, extensive studies have been performed to address the negative impact of landuse zoning ordinances that result in most residential properties being developed at locations featuring highly segregated land uses and curvilinear or cul-de-sac street patterns (Matthews and Turnbull 2007). Substantial distances have been created between residential properties, commercial properties, and ser-vices locations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Matthews and Turnbull (2007) [3] simultaneously analyzed the contrasting effects of retail proximity on residential property value using two different distance measurements: Euclidian distance for the negative externalities of retail sites and network distance for the proximity benefits. When they calculated the composite effect of travel and straight-line distances, the net effect on housing value peaked at about 170 m and disappeared at about 385 m. This sophisticated research serves as evidence that negative externalities emerge within a short distance but are dominated by the convenience factor beyond a certain distance.…”
Section: Externality Effects On Residential Property Valuementioning
confidence: 99%
“…These negative effects are termed "disamenity effects". As previous empirical research has demonstrated conflicting outcomes concerning the effects of commercial land use in a neighborhood, Matthews and Turnbull (2007) [3] explored the trade-off between the proximity effect and the disamenity effect. However, their distance measurements did not account for the impact of the intensity of commercial activity.…”
Section: Introductionmentioning
confidence: 99%
“…Research by Matthews and Turnbull (2007) showed that a grid-like street pattern increases property values in more pedestrian-oriented neighborhoods and decreases property values in autooriented neighborhoods. Other work found that each incremental increase in walkability is associated with an increase in property value of up to 9% (Pivo & Fisher, 2010).…”
Section: Walkability Economic Value and Demandmentioning
confidence: 99%